Spiraling Nested Multiwalled Carbon Nanotubes - Zhang, Bo; Gao, Faming; Hou, Li (Asian Journal of Chemistry, 2011)
The spiraling nested multiwalled carbon nanotubes (sn-MWCNs) with one encapsulated into the other were synthesized using solvothermal method. The growth mechanism of the sn-MWCTs was discussed. The capacitance of the nested nanotube was calculated theoretically via modeling a classical cylindrical capacitor with it.